The Lone Ranger, Tonto, and Katherine: What Is the Script for a Senior Faculty Member?. (March 2020) - Hendrix, Katherine Grace
The qualitative methodological approach of autoethnography is used to compose a narrative relating to my experiences at this stage in my career. More specifically, my inner thoughts as a senior faculty member, nearing the end of her career, are laid bare for the audience. The conflictual nature of deciding when, how, and whether to make an exit is shared across four themes: self-concept, new knowledge, aging, and retirement.